Videocapillaroscopy of the Oral Mucosa in Patients with Diabetic Foot: Possible Diagnostic Role of Microangiopathic Damage? - Giuseppe A. Scardina (Journal of Clinical Medicine, 2020)
Introduction: Diabetic foot represents one of the most serious and expensive complications of diabetes and is subject to a high percentage of amputations that are almost always preceded by ulcers ascribable to neuropathy and/or vasculopathy. Videocapillaroscopy (VCS) can be a valuable aid in order to uncover morpho-structural anomalies in the vascular bed, both at the level of the oral mucosa and at the level of the terminal vessels of the lower limb. Materials and methods: Sixty subjects divided into 4 groups were enrolled: 15 healthy subjects; 15 patients with diabetes for more than 10 years without ulcerative foot lesions; 15 patients with neuropathic diabetic foot (clinical diagnosis, MDNS); 15 patients with ischemic diabetic foot (clinical diagnosis, ABI, lower limb doppler). A complete videocapillaroscopic mapping of the oral mucosa was carried out on each patient. The areas investigated were: labial mucosa, the retro-commissural region of the buccal mucosa, and the vestibular masticatory mucosa (II and V sextant). Results: The analysis of the morphological and densitometric characteristics of the capillaries revealed the following: a significant reduction in capillary density in neuropathic (mean ± SD 7.32 ± 2.1) and ischemic patients (mean ± SD 4.32 ± 3.2) compared to the control group of patients (both diabetic mean ± SD 12.98 ± 3.1 and healthy mean ± SD 19.04 ± 3.16) (ANOVA test and Bonferroni t test p < 0.05); a reduction in the average length of the capillaries and a significant increase in tortuosity (ANOVA test and Bonferroni t test p < 0.05). In the neuropathic patients, a recurrent capillaroscopic pattern that we defined as “sun” was found, with capillaries arranged radially around an avascular area. Conclusions: The data obtained from this preliminary study suggest a potential diagnostic role of oral capillaroscopy in the early and subclinical identification of microangiopathic damage in patients with diabetic foot.